The Effect Fermentation Durian Fruit Waste Use Oyster Mushroom (Pleurotus Ostreatus) on Water, Ash, Crude Fat, and Crude Protein Content - Dewi, Rd Rahma Sandriana; Ramadhan, Rahmad Fani; Rusmana, Denny (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Durian fruit waste is a type of agricultural waste that has a fairly high nutritional content so that it has the potential to be used as a feed source of energy for poultry. This study aims to analyze the effect of fermenting durian fruit waste using oyster mushrooms (Pleurotus ostreatus) on the water, ash, crude fat, and crude protein content of durian fruit waste. The research was conducted from November 2024 to January 2025 at the Mini Feedmill Ciparanje and Non-Ruminant Animal Nutrition and Animal Feed Industry Laboratory at the Faculty of Animal Science, Universitas Padjadjaran. The study was carried out experimentally using a completely randomized design with 5 treatments and 5 replications for each treatment. The treatments were as follows: P0 (unfermented DFW), P1 (fermented DFW with an inoculum dose of P. ostreatus 0.5%), P2 (fermented DFW with an inoculum dose of P. ostreatus 1%), P3 (fermented DFW with an inoculum dose of P. ostreatus 2%), and P4 (fermented DFW with an inoculum dose of P. ostreatus 4%). The results of the study showed that the use of oyster mushrooms (Pleurotus ostreatus) had a significant effect on increasing the levels of water, ash, crude fat, and crude protein in fermented durian fruit waste. The inoculum dose of 1% of oyster mushrooms yielded the best results, with an increase in crude protein content of up to 10.94%.